MANAJEMEN PERPUSTAKAAN DAN MUTU PENDIDIKAN DI SEKOLAH - Agus Fahmi (Jurnal Paedagogy, 2016)
Improving the quality of schools is a must for every educational institution in order to maintain the existence of the institution on an ongoing basis. One of the elements that plays a role in efforts to improve the quality is the school library as a source of information and publications in the form of books, magazines, reports, scientific papers, audio visuals, films, slides, VCDs, DVDs, cassettes and so on. The school library is a very important provider of information for school residents, especially reading materials related to the learning and teaching process, the more references available in the library, the better the quality of learning that occurs. Another thing that must be considered is library management starting from planning, organizing, structuring, recording, book classification, and library funding which is carried out effectively and efficiently. Along with the times, libraries as a support and support for improving the quality of schools, libraries should be equipped with technology such as computers and internet networks (wi-fi), which aim that students, teachers and school stakeholders can enjoy or facilitate access to reading materials. online around the school environment without having to be in the library building. In accordance with what has been described above, improving the quality of the school will be achieved if the goals and benefits of the library have been used optimally.